Gut microbiota composition in COVID-19 hospitalized patients with mild or severe symptoms - Mazzarelli, Antonio; Giancola, Maria Letizia; Fontana, Andrea; Piselli, Pierluca; Binda, Elena; Trivieri, Nadia; Mencarelli, Gandino; Marchioni, Luisa; Vulcano, Antonella; De Giuli, Chiara; Panebianco, Concetta; Villani, Annacandida; et al. (Frontiers in Microbiology, 2022)
Background and aim: COVID-19, the infectious disease caused by SARS-CoV-2 virus that has been causing a severe pandemic worldwide for more than two years, is characterized by a high heterogeneity of clinical presentations and evolution and, particularly, by a varying severity of respiratory involvement. This study aimed to analyze the diversity and taxonomic composition of the gut microbiota at hospital admission, in order to evaluate its association with COVID-19 outcome. In particular, the association between gut microbiota and a combination of several clinical covariates was analyzed in order to carachterize the bacterial signature associate to mild or severe symptoms during the SARS-CoV-2 infection. Materials and Methods: 16S rRNA gene sequencing of 97 rectal swabs from a retrospective cohort of 600 rectal swabs from COVID-19 hospitalized patients was employed to study the gut microbiota composition. Patients were divided in two groups according to their outcome considering the respiratory supports they needed during hospital stay: i) group “mild”, including 47 patients with a good prognosis and who never required non-invasive or invasive ventilation and ii) group “severe”, including 50 patients who experienced a more severe disease due to severe respiratory distress that required non-invasive or invasive ventilation. Identification of the clusters of bacterial population between patients with mild or severe outcome was assessed by PEnalized LOgistic Regression Analysis (PELORA) was performed to identify clusters of bacterial populations with differential abundances. Results: Although no changes for Chao1 and Shannon index were observed between the two groups a significant greater proportion of Campylobacterota and Actinobacteriota at phylum level was found in patients affected by SARS-CoV-2 infection who developed a more severe disease characterized by respiratory distress requiring invasive or non-invasive ventilation. Clusters have been identified with a useful early potential prognostic marker of the disease evolution. Discussion: Microorganisms residing within the gut of the patients at hospital admission, were able to significantly discriminate the clinical evolution of COVID-19 patients, in particular who will develop mild or severe respiratory involvement. Our data show that patients affected by SARS-CoV2 with mild or severe symptoms display different gut microbiota profiles which can be exploited as prognostic biomarkers.